Training tom cats for semen collection using an artificial vagina: a retrospective study - Ackermann, Camila L [UNESP]; Lopes, Maria D [UNESP] (SAGE Publications, 2020)
Objectives: Owing to the lack of literature on training cats to use an artificial vagina (AV), we performed a retrospective study on the success of training tom cats for semen collection using an AV. Methods: Records from training 20 cats (2009 until 2019) for semen collection using AVs were analyzed. Sexual preferences, behavior towards humans, queens and other tom cats, as well as libido, number of training sessions and rate of success were observed. Data are presented as percentages and the results are described subjectively. Results: In 85% of tom cats, collection using an AV was performed successfully. Training was unsuccessful when libido was low or absent. Behavior towards humans did not interfere with the success rate, while libido did. Conclusions and relevance: Most tom cats can be successfully trained to have semen collected using an AV; the number of training sessions required depends on the male’s libido and the technician’s experience.
Keywords: laboratory animals; queen; reproduction; Sperm